(untitled) (Società e diritti, 2020)
Abstract: Aristotle cherishes the idea of social equity despite his deep respect for social diversity and social difference. The end justifies the means as long as we aim to achieve equity and virtue, according to Aristotle. Equity thus determines and rectifies penal justice. Devotion to the ideal of penal justice annuls any relativism in our public experiences of the institutional sanctions that safeguard democracy. However, Aristotle considers a valid system of penal justice as unattainable, believing, as he does, that one cannot ever know whether punishment is socially efficacious. If we think logically, we may see that Aristotle believes that power is inherently weak. Unfortunately, however wide the field of doubts facing us, Aristotle’s material reductionism is traced simply because it is the content of our experience, a reductionist one. Nevertheless, his dismissal of the motives of revenge and utility as nonsensical re-establishes the institutional character of punishment in order to humanise it. Punishment is no longer considered to be a symbol of state-oppression and becomes a symbol of law the fulfillment of which is wisdom without desire for uncontrolled power